Optical Coherence Tomography in Patients with Chronic Migraine: Literature Review and Update - Ascaso, Francisco J.; Marco, Sara; Mateo, Javier; Martínez, Mireya; Esteban, Olivia; Grzybowski, Andrzej (Frontiers in Neurology, 2017)
Migraine is a chronic disease characterized by unilateral, pulsating, and often moderate-to-severe recurrent episodes of headache with nausea and vomiting. It affects approximately 15% of the general population, yet the underlying pathophysiological mechanisms are not fully understood. Optical coherence tomography (OCT) is a safe and reproducible diagnostic technique that utilizes infrared wavelengths and has a sensitivity of 8-10 micrometers. It can be used to measure thinning of the retinal nerve fiber layer (RNFL) in some neurological disorders. Although ophthalmologists are often the first specialists to examine patients with migraine, few studies have addressed the involvement of the optic nerve and retino-choroidal structures in this group. We reviewed the literature on the etiological and pathological mechanisms of migraine and the relationship between recurrent constriction of cerebral and retrobulbar vessels and ischemic damage to the optic nerve, retina, and choroid. We also assessed the role of OCT for measuring peripapillary RNFL thickness and macular and choroidal changes in migraine patients. There is considerable evidence of cerebral and retrobulbar vascular involvement in the etiology of migraine. Transitory and recurrent constriction of the retinal and ciliary arteries causes ischemic damage to the optic nerve, retina, and choroid in patients with migraine. OCT to assess the thickness of the peripapillary RNFL, macula, and choroid might increase our understanding of the pathophysiology of migraine and facilitate diagnosis of retino-choroidal compromise and follow-up of therapy in migraine patients. Future studies should determine the usefulness of OCT findings as a biomarker of migraine.